X-linked chronic granulomatous disease secondary to skewed X-chromosome inactivation in female patients - Zhang, Yue; Shu, Zhou; Li, Yan; Piao, Yurong; Sun, Fei; Han, Tongxin; Wang, Tianyou; Mao, Huawei (Clinical and experimental immunology, 2024)
Background Chronic granulomatous disease (CGD) is a heterogeneous primary immunodeficiency. X-linked (XL) CGD caused by gene defects of CYBB is the most prevalent type of CGD. Objective We aim to understand the clinical and molecule features of XL-CGD secondary to skewed X-chromosome inactivation (XCI) in female. Methods We retrospectively reviewed the medical records of a female patient diagnosed with XL-CGD. Flow cytometry was used to detect the respiratory burst function. After restriction enzyme digestion of DNA, XCI was calculated by detecting fluorescent PCR products with capillary electrophoresis. The previously published female XL-CGD cases secondary to skewed XCI was summarized. Results Clinical data were available for 15 female subjects. The median age of diagnosis was 16 years. Consistent with XL-CGD in males, infection was the most frequent manifestation in the female patients. Catalase-positive pathogens including Serratia marcescens and Staphylococcus aureus infections were the most common pathogens. Autoimmune/autoinflammation manifestations were observed in five patients. Dihydrorhodamine (DHR) assay showed that median %DHR+ values were 6.5% and the values varying with age were observed in 2 patients. All patients had a skewing XCI and there was no consistency between the daughter and carrier mother. Anti-infective treatment was effective in majority and there was no mortality reported in XL-CGD female patients to date. Conclusion XL-CGD should not be neglected in female patients manifested as CGD phenotype and it is necessary to make periodic clinical evaluation of CGD female carriers as the neutrophil oxidative function may decline with aging and increase the risk for infection. X-linked chronic granulomatous disease secondary to skewed X chromosome inactivation in female patients. Detection of X-chromosome inactivation using the highly polymorphic HUMARA locus in combination with adjacent methylation-sensitive restriction sites for HpaII in a patient and her parents. The mutant allele is marked with black arrows. Graphical Abstract Graphical Abstract